Student nurses' perceptions of a patient safety culture: A descriptive and cross‐sectional study. Issue 2 (30th April 2021) - Çiftcioğlu, Şule; Apaydın Cırık, Vildan; Efe, Emine
Abstract: Purpose: The aim of this study was to evaluate nursing students' perceptions of a patient safety culture in one university in Turkey. Design and Methods: The sample of this descriptive cross‐sectional study consisted of 299 undergraduate nursing students. Data were collected by having participants complete the Patient Safety Culture Scale (PSCS) and a personal information form. Findings: Participants' scores on the PSCS were found to be moderate, and no significant differences were found between participants' study levels. Female students and students who had willingly chosen the nursing profession obtained statistically significantly higher scores on the PSCS, indicating positive perceptions of a patient safety culture. Practice Implications: The inclusion of patient safety education and training of nurses in the nursing curriculum may contribute to students' development of a patient safety culture.